2022
DOI: 10.3390/nu14204415
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Intravenous Vitamin C on Neutrophil Extracellular Traps and the Endothelial Glycocalyx in Patients with Sepsis-Induced ARDS

Abstract: (1) Background: The disease-modifying mechanisms of high-dose intravenous vitamin C (HDIVC) in sepsis induced acute respiratory distress syndrome (ARDS) is unclear. (2) Methods: We performed a post hoc study of plasma biomarkers from subjects enrolled in the randomized placebo-controlled trial CITRIS-ALI. We explored the effects of HDIVC on cell-free DNA (cfDNA) and syndecan-1, surrogates for neutrophil extracellular trap (NET) formation and degradation of the endothelial glycocalyx, respectively. (3) Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Aspirin inhibits neutrophil migration and thromboxane-dependent NETs formation by inhibiting platelet-neutrophil interactions ( 301 ). High-dose intravenous vitamin C (HDIVC) improves ARDS by reducing the occurrence of NETosis and the shedding of the vascular endothelial glycocalyx by down-regulating the expression of cell-free DNA in neutrophils and proteoglycan syndecan-1 in vascular endothelial cells ( 302 ). α1-antitrypsin (AAT), as a protease inhibitor, especially a NE inhibitor, inhibits neutrophil migration and NETs formation by binding to IL-8 to inhibit CXCR1/CXCL8 signaling axis ( 303 ).…”
Section: Potential Therapeutic Targets For Septic Ardsmentioning
confidence: 99%
“…Aspirin inhibits neutrophil migration and thromboxane-dependent NETs formation by inhibiting platelet-neutrophil interactions ( 301 ). High-dose intravenous vitamin C (HDIVC) improves ARDS by reducing the occurrence of NETosis and the shedding of the vascular endothelial glycocalyx by down-regulating the expression of cell-free DNA in neutrophils and proteoglycan syndecan-1 in vascular endothelial cells ( 302 ). α1-antitrypsin (AAT), as a protease inhibitor, especially a NE inhibitor, inhibits neutrophil migration and NETs formation by binding to IL-8 to inhibit CXCR1/CXCL8 signaling axis ( 303 ).…”
Section: Potential Therapeutic Targets For Septic Ardsmentioning
confidence: 99%
“…These candidates primarily target the expression of EG degradation products, like syndecan-1, or enzymes like HPA. Clinical studies have shown that high-dose intravenous vitamin C can significantly reduce ARDS-associated syndecan-1 levels, further validating EG as an effective therapeutic target ( Qiao et al, 2022 ). Secondly, EG-related biomarkers are being examined in clinical studies to determine their reliability as indicators for ARDS diagnosis or prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C and recombinant thrombomodulin have also been investigated to preserve the glycocalyx and improve outcomes in sepsis. In humans, 48 h of high-dose intravenous vitamin C (50 mg/kg every 6 h) lowered plasma syndecan-1 concentrations [60]. Treatment recombinant thrombomodulin normalized glycocalyx characteristics in septic mice demonstrated by lower plasma syndecan-1 concentrations after treatment [59].…”
Section: Sepsismentioning
confidence: 97%